The story of Langjökull ice tunnel - Sif Pétursdóttir 1992- (2023)
The deformation of glacial ice is dependent on many variables which can be hard to measure. A 500-meter man-made tunnel has been constructed at 1250 m a.s.l. altitude in Langjökull glacier, Iceland. The deformation of the tunnel, the temperature of the ice and the density of the ice at several places inside the tunnel have been observed. Glacial ice behaves as a thick viscous fluid that slowly and continuously deforms under applied stress. The focus of this research project is on modelling the deformation and ice flow in Langjökull around the ice tunnel using the model Elmer/Ice to solve the Stokes equations to compute stress and velocity fields in 3D. Combining numerical modelling of the glacier with topographic measurements of the tunnel we try to get the full story of how the real movement of the tunnel and the glacier compares with the solution of the numerical model. The simulated velocities are compared to measured surface velocities and an estimate for the prefactor of the creep parameter A is determined. From the initial topographic measurements in 2015 to the latest readings in 2023, the tunnel has shifted horizontally by a distance of 91 ± 1 meters. In addition, there has been a vertical descent of the glacier at a rate of 2.8 ± 0.2 meters per year between 2015 and 2023. The results from the model and the topographic measurements give a better insight into how long this tunnel will last and how it deforms and moves in the glacier over time. Aflögun jökulíss er háð mörgum breytum sem erfitt getur verið að mæla. Gerð hafa verið 500 metra manngerð göng í u.þ.b. 1250 m hæð í Langjökli. Fylgst hefur verið með aflögun ganganna, hitastigi íssins og eðlismassa á nokkrum stöðum inni í göngunum. Jökulís hegðar sér eins og þykkur seigfljótandi vökvi sem hægt og stöðugt aflagast undan eigin þunga. Áhersla þessa rannsóknarverkefnis er að skoða aflögun og ísflæði í Langjökli í kringum ísgöngin með því að nota líkanið Elmer/Ice til að leysa Stokes jöfnur til að reikna spennu- og hraðasvið í þrívídd. Með því að ...